Problemas derivados de la imposibilidad de demandar el divorcio por voluntad unilateral, en el cantón Machala, periodo 2012-2013. - Feijoo Encalada, María José (2014)
In this research, we defended our hypothesis that the inability to sue for divorce by unilateral will, in Canton Machala in the province of El Oro in the period 2012-2013, comes to injure the constitutional right to freely develop personality without more limited than the rights of others, as the person who does not want to be married is legally obliged to maintain personal ties.